2021
DOI: 10.3390/en14144339
|View full text |Cite
|
Sign up to set email alerts
|

Seaports during the COVID-19 Pandemic: The Terminal Operators’ Tactical Responses to Disruptions in Maritime Supply Chains

Abstract: The world-wide crisis caused by the Coronavirus disease 2019 (COVID-19) pandemic had a significant impact on the global economy functioning and the sustainable development of supply chains. The changes also affected seaports being the key links of maritime supply chains. The purpose of the research study described in this article was to identify the sources and kinds of disruptions observed in various maritime supply chains as a result of the COVID-19 pandemic and their impact on the operations of various type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Apart from analyzing COVID-19 from global perspectives, numerous researches focus on gathering data on the effects of the COVID-19 pandemic on the maritime industry (Guerrero et al , 2022; Menhat et al , 2021; Millefiori et al , 2021; Narasimha et al , 2021; Oyenuga, 2021; Saviolakis and Pazarzis, 2021; Shi and Weng, 2021; Tai et al , 2021). To illustrate, Menhat et al (2021) discussed the impact of the pandemic on four areas, namely, shipping, fisheries, maritime tourism and oil and gas sector; Mańkowska et al (2021) analyzed the response of seaport terminal operators concerning COVID-19; and Charłampowicz (2021) explored the service quality of sea transportation during the pandemic period. Furthermore, Wang et al (2021) assessed the ship management efficiency index based on congestion perspectives, which is relevant as the health measures implemented by the government authorities such as safe distancing, quarantines arrangement and travel restrictions would lead to a decrease in productivity at ports and cargo handling operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from analyzing COVID-19 from global perspectives, numerous researches focus on gathering data on the effects of the COVID-19 pandemic on the maritime industry (Guerrero et al , 2022; Menhat et al , 2021; Millefiori et al , 2021; Narasimha et al , 2021; Oyenuga, 2021; Saviolakis and Pazarzis, 2021; Shi and Weng, 2021; Tai et al , 2021). To illustrate, Menhat et al (2021) discussed the impact of the pandemic on four areas, namely, shipping, fisheries, maritime tourism and oil and gas sector; Mańkowska et al (2021) analyzed the response of seaport terminal operators concerning COVID-19; and Charłampowicz (2021) explored the service quality of sea transportation during the pandemic period. Furthermore, Wang et al (2021) assessed the ship management efficiency index based on congestion perspectives, which is relevant as the health measures implemented by the government authorities such as safe distancing, quarantines arrangement and travel restrictions would lead to a decrease in productivity at ports and cargo handling operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 7 ] have found that the fuel and commodity prices and the financial markets are considered to be the main determinates of the shipping market. Also, Mańkowska et al [ 23 ] have shown that the spread of COVID-19 has differently impacted maritime supply chains. Moreover, some of them are completely closed, while some have the lowest operations and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To discover new opportunities and adapting to service offers, transportation business must change their supply chain strategy. For the cargo ship, it is advised to change their storage period to fit customers' needs and decrease cargo turnover [43].…”
Section: Conversation (5): Supply Chain Management and Transportation...mentioning
confidence: 99%